Speak up - Paul, Miranda (Clarion Books, Houghton Mifflin Harcourt, 2020)
Illustrations and easy-to-read, rhyming text encourage the reader to speak up about everything from their own name being mispronounced to someone bring a weapon to school. Includes author's note about real people who have found their voices, when to speak up, and how to express oneself without speaking.